2022
DOI: 10.2174/1381612828666220907102606
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Research in Cellular Pharmacokinetics and its Cutting-edge Technologies

Abstract: Pharmacokinetics (PK), as a significant part of pharmacology, runs through the overall process of the preclinical and clinical research on drugs and plays a significant role in determining the material basis of efficacy and mechanism research. However, due to the limitations of classical PK, cellular PK was put forward at the historic moment and developed rapidly. Many novel and original technologies have been innovatively applied to the cellular PK research, thereby providing a powerful technical support. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Intracellular pharmacokinetics is the study of the kinetic process of absorption, transport, distribution, metabolism, and excretion of drugs in cells and subcells as a microscopic whole [ 19 ]. An increasing amount of research has found that classical pharmacokinetics cannot fully explain the pharmacological effects of drugs in specific tissues or cells, so it is challenging to accurately predict the efficacy of drugs in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular pharmacokinetics is the study of the kinetic process of absorption, transport, distribution, metabolism, and excretion of drugs in cells and subcells as a microscopic whole [ 19 ]. An increasing amount of research has found that classical pharmacokinetics cannot fully explain the pharmacological effects of drugs in specific tissues or cells, so it is challenging to accurately predict the efficacy of drugs in vivo.…”
Section: Introductionmentioning
confidence: 99%